PROSPEK PENGATURAN TINDAKAN KEBIRI KIMIA DAN PEMASANGAN ALAT PENDETEKSI ELEKTRONIK DALAM HUKUM POSITIF DI INDONESIA - Rahmawati, Adellia; Yuningsih, Henny; Nugraha, Adrian (Faculty of Law, University of Palembang, 2024)
Sexulall crimes algalinst children in Indonesial alre very worrying. Perpetraltors of sexulall violence algalinst children alre ulsulallly aldullts who alre close to the victim, whether in the falmily environment or the people in the environment where the child lives. Balsed on this, the government crealted al criminall lalw policy throulgh the formullaltion provisions in Lalw no. 17 of 2016 concerning the Stipullaltion of Government Regullaltions in Lieul of Lalw no. 1 of 2016 concerning the Second Almendment to Lalw no. 23 of 2002 concerning Child Protection Becomes al lalw thalt regullaltes chemicall calstraltion alnd the installlaltion of electronic detection devices for perpetraltors of sexulall violence algalinst children. Chemicall calstraltion is calrried oult by introdulcing alnti-alndrogen chemicalls, either vial pills or injections, into al person's body to wealken the testosterone hormone. In simple terms, chemicalls thalt alre pult into the body will redulce or even eliminalte libido or sexulall desire. The chemicall calstraltion alction formullalted in Alrticle 81 Palralgralph (7) of Lalw no. 17 of 2016 is not in alccordalnce with hulmaln rights. The alct of chemicall calstraltion hals the effect of losing al person's right to continule their offspring alnd fullfill their balsic needs als gulalralnteed in